(3OhQ GdJYbd aj JYOjd GdYdGbI Hjf GdJYdb hGdQVG GdRhGLj (B/s - (3,JSfje YHO GdaJGM SdjeGf eMeO hGdjs; (3eYJR SjO YHO Gddgs; (3UaGA ESeGYjd eQSj s (2025)
(3ojTjQ GdJQGK Edi Cf dCSdhHj GdJYdb ZjQ GdBef OhkQG egkeG aj JMOjO LhOI GdYdGbI eYQakjG hGfaYGdkjG hSdhckjG, hJMbjb GdQVG GdRhGLj; hCf GdJYbd jQJHW HGdQVG GdRhGLj(B. (3hbO gOaJ gPg GdOQGSI Edi eYQaI eG EPG cGfJ OQLI JYbd GdaQO oJnYpqOd ef GdYdGbI GdGQJHGWjI GdSGdHI Hjf CSdhHqj GdJYdb ZjQ GdBef (B((3Gdnbpdb hGdJLfHj(B) (3hGdQVG GdRhGLj ddaQO faSg(B. (3hJe GdJMbb ef gPG ef NdGd JWHjb ebjGS GdJYbd GdTGed (B(CHIME) (3hebjGS GdNHQGJ aj GdYdGbGJ GdhKjbI GdoenYnqOd (B(ECR-R) (3hebjGS GdQVG GdRhGLj Ydi KdGK YjfGJ; GKfJjf GSJWdGYjJjf (B((3f(B1 = 33) (3h(B((3f(B2 = 47) (3hYjfI CSGSjI (B((3f(B3 = 201)(3, ef GdeJRhLjf hGdefLHjf(B. (3hCSaQJ GdfJGFL Yf hLhO GQJHGW OGd EMUGFkjG Hjf eJZjQGJ GdOQGSI aj GdYjfJjf GdKGfjI hGdKGdKI, eG YOG GdGQJHGW Hjf GdJYbd hGdJYdb Gdnbpdb aj GdYjfI GdKGdKI de jcf OGkd EMUGFkjG; hGJVM Cf KdGKI echfGJ ddJYbd (B((3GdhYj HGdJUQa, hJbHd GdNHQI Ohf EUOGQ CMcGe, hGdhYj HGdNHQI Ohf JeQcR Ch JSQY(B) (3JQJHW HGdQVG GdRhGLj Ohf ZjQgG ef GdechfGJ GdCNQi; hXgQ GdJCKjQ GdoeYpqOd ddJYbd aj GdYdGbI Hjf GdJYdb GdJLfHj hGdQVG GdRhGLj aj GdYjfI GdKGfjI abW(B. (3hJeJ efGbTI GdfJGFL aj VhA GdOQGSGJ GdSGHbI, hGdETGQI Edi HYV GdaQhb GdLfOQjI, hGdJhUjGJ ddHMhK GdeSJbHdjI(B.s
This study aimed to determine whether an individual's level of Mindfulness moderates the negative correlation between insecure Attachment styles (anxious and avoidant) and the individual's Marital satisfaction. This was examined by applying the Comprehensive Mindfulness Scale (CHIME), the Experiences in Close Relationships Scale (ECR-R), and the Marital Satisfaction Scale on three samples: (N1= 33), and (N2= 47), and (N3 = 201) of married individuals with children. The results revealed a statistically significant correlation between the study variables in the second and third samples, except for the correlation between mindfulness and anxious attachment in the third sample, which was not statistically significant. It was found that three components of mindfulness (Acting with awareness, Acceptance without judgment, and Nonreactive decentering) are associated with marital satisfaction more than other components. The moderating effect of mindfulness on the relationship between avoidant attachment and marital satisfaction was observed only in the second sample. The results were discussed in terms of previous studies, noting some gender differences, and recommendations for future research.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2025. s
(3HHdjhLQGajG(B: (3UaMGJ (B143-169.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdCRhGL h GdRhLGJs; (3fXQjI GdJYdbs -- (3CSGdjH GdJYdb ZjQ GdBefs -- (3CSdhH GdJYdb Gdbdbs